2011
DOI: 10.1111/j.1755-0238.2011.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delaying budburst on shoot development and yield of Vitis vinifera L. Chardonnay ‘Mendoza’ after a spring freeze event

Abstract: Background and Aims:  Spring freeze events can result in substantial grapevine yield losses in many parts of the world. Understanding vine responses following early spring freeze events will aid in the development of decision support systems for vineyards damaged by freezing temperatures. Methods and Results:  The date of budburst of spur‐pruned Chardonnay vines was manipulated by pruning time and/or the application of sodium alginate gel. A spring freeze event occurred at bud swell/woolly bud, killing 33% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 11 publications
4
32
0
Order By: Relevance
“…Warming has advanced the harvest and hastened ripening in recent decades, thus higher TSS in grapes are attained earlier and ahead of other relevant fruit attributes related to colour, flavour and aroma (Jones et al , Sadras et al , Sadras and Moran ). Late pruning has been used to reduce the risk of frost and improve fruitset in cool climate regions such as New Zealand (Friend and Trought , Friend et al ). More recently, we have tested late pruning as a practice to shift development and improve adaptation to warming in the Barossa Valley of Australia (Moran et al , Petrie et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Warming has advanced the harvest and hastened ripening in recent decades, thus higher TSS in grapes are attained earlier and ahead of other relevant fruit attributes related to colour, flavour and aroma (Jones et al , Sadras et al , Sadras and Moran ). Late pruning has been used to reduce the risk of frost and improve fruitset in cool climate regions such as New Zealand (Friend and Trought , Friend et al ). More recently, we have tested late pruning as a practice to shift development and improve adaptation to warming in the Barossa Valley of Australia (Moran et al , Petrie et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Late spur pruning performed when buds are at the woolly stage has been traditionally used in cool climates to delay budburst and avoid spring frost consequences (Howell and Wolpert , Trought et al , Friend et al ). The delay achievable with such a technique is in the order of a few days and is typically maintained until around flowering.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a good compromise across all risk categories should imply a temperature threshold that represents frost risk more broadly across the survey responses, and hence, more likely to resemble frost damage as experienced by winegrowers. This is compounded further since different cultivars are susceptible to frost damage at various minimum temperature values depending on the time of the frost, environmental conditions and the phenological stage of the crop (Fuller and Telli 1999, Trought et al 1999, Fennell 2004, Friend et al 2011. This suggested that there were possible underestimations associated with mapped frost risk values at these locations.…”
Section: Evaluation Of the Frost Predictions To Survey Responsesmentioning
confidence: 99%
“…Alternatively, response bias from survey respondents may have also systematically predisposed respondents to favour the most extreme option according to their own personal bias, or paradoxically, influence underestimation to the least severe option (Paulhus 1991). This is compounded further since different cultivars are susceptible to frost damage at various minimum temperature values depending on the time of the frost, environmental conditions and the phenological stage of the crop (Fuller and Telli 1999, Trought et al 1999, Fennell 2004, Friend et al 2011. In other words, respondents may portray the degree of frost damage catered specifically to their own cultivar and management regimes and not reflect frost events consistent with other vineyard sites.…”
Section: Evaluation Of the Frost Predictions To Survey Responsesmentioning
confidence: 99%